Who knows, who cares?: The determinants of enactment, awareness, and compliance with community natural resource management regulations in Uganda - Nkonya, Ephraim M.; Pender, John L.; Kato, Edward (Cambridge University Press, 2008)
At the community level, bylaws and other regulations are commonly used to manage natural resources. However, there is limited research on how communities enact these regulations and what determines awareness and compliance with these regulations. A survey of 273 communities was conducted in Uganda with an objective of analyzing the determinants of enactment, awareness and compliance with community Natural Resource Management (NRM) regulations. Presence in the community of programs and organizations with focus on agriculture and the environment increases the probability to enact and to be aware of NRM regulations. The probability to comply with regulations enacted by village councils was greater than the case with such regulations passed by higher legislative bodies, suggesting the important role played by decentralization in NRM. Poverty is associated with lower compliance with NRM regulations. This supports the poverty-natural resource degradation trap hypothesis, and suggests that measures to reduce poverty can also improve NRM.